MENUMBUHKAN SIKAP POSITIF SISWA DALAM PEMBELAJARAN IPS DI SEKOLAH SEBAGAI FONDASI PENDIDIKAN KARAKTER KONTEKSUAL - Mahpudz, Asep (Vidya Karya Jurnal Kependidikan, 2013)
Harmony Education developed a model of the development process that reveals the social studies education of local cultural valuesÂ Â as social capital for learning in social studies education. Harmony Education developed childrenâs interactions at school, the childâs relationship with himself, his relationship with others, and the childâs relationship with the natural world, the so-called selfharmony, harmony fellow and harmony of nature. The goal of education is to develop the character Harmony contextual nature of the potential of humans as individuals, as well as social beings and creatures of God Almighty. This is in accordance with the Education Social Studies in school. The objective of teaching and learning achieved is to develop mutual respect, understanding, caring and sharing compassion, social responsibility, tolerance of diversity between individuals and groups (ethnic, social, cultural, religious). Harmony Education also develops the participation of parents to support the learning process by establishing classroom community.